Pain control with ibandronate for bone marrow oedema of the knee (Swiss Medical Weekly, 2020)
INTRODUCTION Bone marrow oedema is a disabling disease characterised by severe bone pain (with or without prior trauma), insufficient response to analgesics, and reduction of weight bearing. Several studies showed promising results after using bisphosphonates to inhibit osteoclast activity. The aim of this study was to investigate the association between ibandronate administration and pain relief in patients with bone marrow oedema of the knee, and to precisely describe its presentation in magnetic resonance imaging (MRI). METHODS This is a single-centre, retrospective analysis of 18 patients who received intravenous ibandronate due to bone marrow oedema of the knee between April 2012 and February 2016. Information has been extracted from our clinical database and a questionnaire. Furthermore, an experienced radiologist reassessed all MRI diagnoses. RESULTS Our results showed a significant reduction of pain from 7.4 to 3.8 points on the visual analogue scale (p = 0.0001; median follow-up 41.5 months). Furthermore, the disability in daily life also significantly decreased (p = 0.008); 55.6% of the participants stated to be pain-free in the follow-up, and the same percentage also did not use alternative therapies after completing therapy with ibandronate (e.g., regular use of analgesics, operation, or local infiltration). However, there was no significant correlation between pain and specific radiologic findings. CONCLUSIONS Participants with bone marrow oedema of the knee showed a significant pain reduction after an administration of ibandronate, independently of the severity showed in MRI. If the first administration leads to an insufficient control of pain, the administration of a second dose may be helpful. As bone marrow oedema syndrome is a self-limiting disease, prospective studies with a comparison group are needed to distinguish between the natural course of the disease and the beneficial effects of bisphosphonates.